2017
DOI: 10.3390/nu9020117
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Flavonols on Cardiometabolic Biomarkers: A Meta‐Analysis of Randomized Controlled Human Trials to Explore the Role of Inter‐Individual Variability

Abstract: Several epidemiological studies have linked flavonols with decreased risk of cardiovascular disease (CVD). However, some heterogeneity in the individual physiological responses to the consumption of these compounds has been identified. This meta-analysis aimed to study the effect of flavonol supplementation on biomarkers of CVD risk such as, blood lipids, blood pressure and plasma glucose, as well as factors affecting their inter-individual variability. Data from 18 human randomized controlled trials were pool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
89
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 56 publications
3
89
1
Order By: Relevance
“…We show, for first time, that the significant effects of ET-rich products on T-C, LDL, TAGS and DBP and of ANC-rich food products on T-C, DBP and SBP were consistently observed in participants with BMIs ≥ 25 kg/m 2 (overweight/obese). Similar results were found in a previous meta-analysis, looking at the effects of flavanol-containing products in T-C [29]. Together, these results suggest that supplementation with polyphenol-rich products may have a beneficial impact on some cardiometabolic risk factors in overweight and/or obese people.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We show, for first time, that the significant effects of ET-rich products on T-C, LDL, TAGS and DBP and of ANC-rich food products on T-C, DBP and SBP were consistently observed in participants with BMIs ≥ 25 kg/m 2 (overweight/obese). Similar results were found in a previous meta-analysis, looking at the effects of flavanol-containing products in T-C [29]. Together, these results suggest that supplementation with polyphenol-rich products may have a beneficial impact on some cardiometabolic risk factors in overweight and/or obese people.…”
Section: Discussionsupporting
confidence: 88%
“…There are important differences between studies for a number of key factors (body mass index (BMI), sex, smoking habits, diet, health status) that likely influence the response of the participants to the intake of the compounds tested. These differences can mask significant effects in specific populations [28,29]. …”
Section: Introductionmentioning
confidence: 99%
“…This varied from one participant excreting 8 out of 17 phenolic acids to another excreting 17 out of 17 phenolic acids. This is particularly relevant as inter-individual variability in the response to (poly)phenolics (including flavonols) is now being increasingly considered [61]. However, whether inter-individual variability of (poly)phenols metabolism suggests a biological difference between the age groups is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…According to meta-analyses quercetin supplementation was associated with a positive effect on blood lipid profile. It was observed in small but significant decrease in total cholesterol, LDL cholesterol and triacylglycerol and significant increase in HDL cholesterol [5].…”
Section: Introductionmentioning
confidence: 91%
“…Quercetin protects blood vessels from the damaging effects of oxidative stress, especially from lipid peroxidation, decreases blood pressure, leads to lowering of LDL cholesterol and causes cardioprotective effect. Results from human randomized controlled trials showed that flavonol consumption, especially quercetin, improved biomarkers of CVD risk [5]. Dietary supplementation with quercetin significantly reduced systolic blood pressure in overweight subjects with a high CVD risk and decreased plasma oxidised LDL concentrations that reflects cardioprotective effect of flavonoid [6].…”
Section: Introductionmentioning
confidence: 99%